Higher Education of Yemen: History, Development and Current Status - Al-haimi, Basheer; Mohd. Rashid, Ab. Hamid; Hujainah, Fadhl (Universiti Malaysia Pahang, 2017)
Higher education is new in Yemen compared to advanced countries, where began the establishment of Sana'a University in 1970 and Aden University in 1975.On this paper, researcher embarked on a review study related to the history and development of Higher Education in Yemen. This paper heavily depends on the literature exploration as a secondary source of data collection, while the primary data collection was relying on the information gained throughout the interview with the top management of the higher education of Yemen. The findings show the current status of Yemen Higher Education and the current roles of its institutions that have been evaluated based on the experts’ opinions.